2019
DOI: 10.1186/s12909-019-1703-y
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspectives on undergraduate oral surgery education

Abstract: Purpose This study evaluated students’ perceptions of their self-confidence regarding aspects of their undergraduate oral and maxillofacial surgical training. It further aimed to develop a reliable Turkish version of the questionnaire originally developed by the Association of British Academic Oral Maxillofacial Surgeons (ABAOMS) Education Committee. Methods A cross-sectional survey of 40 fourth-year and 47 fifth-year dentistry students of Yeditepe University Faculty of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 19 publications
12
27
0
Order By: Relevance
“…On the other hand, the students had performed simple extractions on healthy patients in whom haemorrhage is easy to control. In line with previous studies, lower confidence levels were reported in recognition of potential malignant pathologies and skills to differentiate between odontogenic pain and non‐odontogenic pain . This may be due to the low incidence of malignancies presenting at student clinics.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…On the other hand, the students had performed simple extractions on healthy patients in whom haemorrhage is easy to control. In line with previous studies, lower confidence levels were reported in recognition of potential malignant pathologies and skills to differentiate between odontogenic pain and non‐odontogenic pain . This may be due to the low incidence of malignancies presenting at student clinics.…”
Section: Discussionsupporting
confidence: 86%
“…Whilst the majority of the respondents were females, which represented the shift of dental workforce, the male respondents were more confident in all aspects of elevator and forceps use with surgical extraction in line with previous studies . However, this result was in contrast with a previous adaptation questionnaire, which was conducted at a private dental school in Istanbul with a small sample size . The result here may reflect either part of personal makeup or reduced exposure to surgical extraction by female respondents, and these differences in data may be attributed to the increased number of participants and might be related to the higher level of confidence in the anatomical knowledge of the male respondents as well.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…[3,4,6,7] The Association of British Academic Oral Maxillofacial Surgeons (ABAOMS) educational committee have constructed a thorough and validated questionnaire instrument to assess the self-con dence of the dental students according to their undergraduate oral and maxillofacial surgery teaching and have been used in several countries. [7][8][9][10] The ABAOMS instrument is made of 17 questions assessing the student's con dence in performing oral surgery procedures, role of outreach in oral surgery, anatomy teaching in relation to oral surgery, and oral surgery career aspiration. [7] The Faculty of Dentistry at Kuwait University started the undergraduate Oral and Maxillofacial Surgery teaching curriculum in 2002, when the dental students started their clinical years.…”
mentioning
confidence: 99%